Spatiotemporal Dynamics of Habitat Quality in Semi-Arid Regions: A Case Study of the West Songnen Plain, China - Hao Yu; Zhimin Liang; Rong Zhang; Mingming Jia; Shicheng Li; Xiaoyan Li; Huiying Li (Remote Sensing)
Maintaining or improving habitat quality is essential for conserving biodiversity and ensuring the long-term survival of species. Nevertheless, increasing global warming and intensifying human activities have led to varying degrees of habitat degradation and biodiversity loss, especially in semi-arid regions. Focusing on China’s West Songnen Plain—the nation’s largest saline-alkali region confronting acute environmental challenges—this study introduced the soil salinization level and mean NDVI of farmland during the growing season as dynamic threat factors and systematically explored the spatiotemporal dynamic characteristics of habitat quality in the semiarid area of the West Songnen Plain from 1990 to 2020. The results showed the following: (1) Habitat quality exhibited a continuous decline during the study period, following a “degradation–recovery” trajectory with deterioration peaking in 2010; the low- and poor-quality habitats predominantly distributed in the central areas characterized by severe salinization, interspersed with patches of good-quality habitat. (2) The degradation of habitat quality was mainly concentrated in natural land cover types, whereas improvements were observed locally in farmland and bare land. However, slight opposite trends were detected between the mean habitat quality values and the habitat change areas in forests, waters, and bare land. As the elevation continuously increased, the habitat quality grade shifted towards better conditions. (3) A spatial autocorrelation analysis revealed a significant clustering of habitat quality, but the extent of hot spots and cold spots gradually shrank as grassland degradation and saline land management progressed. By incorporating dynamic threat factors and integrating multi-source data, this study improved the habitat quality assessment framework for semi-arid regions and provided scientific support for spatially stratified conservation strategies.